Profil Kondisi Fisik Dominan Atlet Putra Tim Pon XX Rugby 7’s Papua: Profil Kondisi Fisik Dominan Atlet Putra Tim Pon XX Rugby 7’s Papua - Taplo, Ngawok; Womsiwor, Daniel; Hasan, Baharuddin (Indonesia, 2023)
This research aims to determine the profile of the dominant physical condition of male athletes from the PON XX Rugby 7 Papua team. The method used is the survey method. The research sample used total sampling, namely 12 athletes. The analysis technique used is quantitative descriptive analysis technique with percentages. The research variables are 5 components of rugby's dominant physical condition which are the test items: Strength, Speed, Power, Agility, Endurance. The results of the study showed that of the 12 athletes, only a few categories met and the remaining 0% or 0 people, including: Strength (squat) athletes were in the category ''very good'' 83.33% or 10 people and the category